2002
DOI: 10.1002/psc.421
|View full text |Cite
|
Sign up to set email alerts
|

SPPS of protected peptidyl aminoalkyl amides

Abstract: Monophthaloyl diamines derived from naturally occurring amino acids were attached through their free amino functions to resins of the trityl type. The phthaloyl groups were removed by hydrazinolysis, and peptide chains were assembled using Fmoc/tBu-amino acids on the liberated amino functions. The peptidyl aminoalkyl amides obtained were cleaved from the resins by mild acidolysis, with the tBu-side chain protection remaining intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To address the aforementioned issues, we began to explore alternative approaches for the synthesis of the key phenacyl halide functionality. We postulated that such a functionality could be incorporated using Friedel−Crafts chemistry, and evaluation of the literature showed that the amino phthalimide 11 , accessible from l -phenylalaninol 12 , was a known compound that could serve as a substrate for just such an alternative approach to GSK923295A via the phthalimide intermediate 11 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…To address the aforementioned issues, we began to explore alternative approaches for the synthesis of the key phenacyl halide functionality. We postulated that such a functionality could be incorporated using Friedel−Crafts chemistry, and evaluation of the literature showed that the amino phthalimide 11 , accessible from l -phenylalaninol 12 , was a known compound that could serve as a substrate for just such an alternative approach to GSK923295A via the phthalimide intermediate 11 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The approach that we introduce here [2] involves the use of a 2-chlorotrityl chloride (CTC) resin, a polymer support functionalized with chlorotrityl groups. These groups graft nucleophiles, such as thiols, [12] amines [13] and carboxylates, [14] allowing cleavage of the final product under mild acidic conditions. In addition, this resin has the advantage that it can be regenerated several times, [15] a fact supported by other studies by our group.…”
Section: Introductionmentioning
confidence: 99%